2016
DOI: 10.5812/traumamon.20773
|View full text |Cite
|
Sign up to set email alerts
|

Association Between the Pancreatic Enzyme Level and Organ Failure in Trauma Patients

Abstract: BackgroundThe literature suggests an association of pancreatic enzymes with systemic inflammation resulting in secondary organ injury and dysfunction following trauma. Elevation in serum enzymes may not always be predictive of pancreatic disease, and can reflect extra pancreatic production.ObjectivesThis study was conducted to evaluate the rise in serum pancreatic enzyme levels with the incidence of organ failure following trauma.Patients and MethodsA retrospective review was performed on critically injured pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…This is to state that follow up of serum amylase cannot be used as a predictor for volume of extra-pancreatic necrosis and indirectly, organ failure. The results were similar to the study done by Subramanian et al 17 In their study also, they found no significant correlation between the amylase level and organ failure. There was a significant relationship between the increase in duration of the hospital stay and increased EPN volume in our study.…”
Section: Discussionsupporting
confidence: 91%
“…This is to state that follow up of serum amylase cannot be used as a predictor for volume of extra-pancreatic necrosis and indirectly, organ failure. The results were similar to the study done by Subramanian et al 17 In their study also, they found no significant correlation between the amylase level and organ failure. There was a significant relationship between the increase in duration of the hospital stay and increased EPN volume in our study.…”
Section: Discussionsupporting
confidence: 91%
“…However, the ICU length of stay and the duration of mechanical ventilation were significantly higher in patients with increased pancreatic enzymes. Similarly, Subramanian et al [ 14 ] reported that the level of serum lipase was positively correlated with the incidence of organ failure in critically ill trauma patients. In patients with septic shock, Pizzelli et al [ 15 ] reported that all the 21 included patients had increased pancreatic enzymes but none of them had clinical or radiological abnormalities suggesting acute pancreatitis.…”
Section: Discussionmentioning
confidence: 94%
“…Mechanical ventilation was started on admission to the ICU in 32 patients (64%). Median duration of mechanical ventilation was 5 [ 2 14 ] days. All of our patients were started on enteral feeding within the first 24 h of admission and none of them received parenteral nutrition.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clues to the role of adipose composition in severity come from studies from Western populations showing a BMI of >30 mostly, but not always (2, 3) associated with severity, while in Eastern populations, much lower BMIs, sometimes ≥23 (8,9), are associated with severity. This "obesity paradox" (10) also occurs in other acute scenarios such as burns (11), acute heart failure (12), after trauma (13), cardiovascular surgery (14), and during critical illnesses (15) in which elevated pancreatic enzymes (16)(17)(18) and long-chain NEFA (19,20) have been associated with severity. More recent studies associate such an enzyme leak (21) and dietary fat composition (22), along with elevated NEFA levels, to the severity (23) and mortality from coronavirus disease 2019 (COVID-19) (22,24).…”
Section: Introductionmentioning
confidence: 99%